Determining the Impact of Cultural Diversity on Regional Economies in Europe - Dirk Dohse; Robert Gold (WWWforEurope, 2014)
In recent decades, the ethnic composition of the European population has changed substantially, leading to a rapid increase of cultural diversity in the EU as a whole, at the level of individual member states, and at the regional level. This paper focusses on the regional level and investigates the relationship between cultural diversity and regional economic performance for the EU 27. Giving particular attention to regional innovation, GDP per capita, and its development over time, the paper finds that culturally more diverse regions are on average more innovative, which translates into higher growth and better economic performance. An important finding of this study is, however, that the positive effect of cultural diversity on regional economic performance is not present in all sub-samples of the European regions alike.
Keywords: M13; O18; R11; 330; Regional Development; Cultural Diversity; Measurement Issues